Towards Digital Enlightenment Essays on the Dark and Light Sides of the Digital Revolution - Helbing, Dirk.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This new collection of essays follows in the footsteps of the successful volume Thinking Ahead - Essays on Big Data, Digital Revolution, and Participatory Market Society, published at a time when our societies were on a path to technological totalitarianism, as exemplified by mass surveillance reported by Edward Snowden and others. Meanwhile the threats have diversified and tech companies have gathered enough data to create detailed profiles about almost everyone living in the modern world - profiles that can predict our behavior better than our friends, families, or even partners. This is not only used to manipulate peoples' opinions and voting behaviors, but more generally to influence consumer behavior at all levels. It is becoming increasingly clear that we are rapidly heading towards a cybernetic society, in which algorithms and social bots aim to control both the societal dynamics and individual behaviors.<span lang="EN-US" style="font-family: However there are also silver linings: most of the threats that have accumulated over the past years have been identified and regulations are on the way to being introduced. Furthermore, entirely novel approaches based on blockchain technology and other developments derived from complexity science offer the possibility of entirely redefining collective trust and building platforms to support our core societal values. <span lang="EN-US" style="font-family: This book conveys an encouraging vision of the future and provides a sketch of how it may look: The road to digital enlightenment is still open, but it needs to be taken now.
Preface -- The World Today: A Net Assessment, by Dirk Helbing -- Why Our Innovation System Is Failing - and How to Change This, by Dirk Helbing- and How to Change This, by Dirk Helbing -- The Hidden Danger of Big Data, by Carlo Ratti and Dirk Helbing -- Machine intelligence: Blessing or curse? It depends on us!, by Dirk Helbing -- An Extension of Asimov's Robotics Laws, by Jan Nagler, Jeroen van den Hoven and Dirk Helbing -- Societal, Economic, Ethical and Legal Challenges of the Digital Revolution: From Big Data to Deep Learning, Artificial Intelligence, and Manipulative Technologies, by Dirk Helbing -- Will Democracy Survive Big Data and Artificial Intelligence?, by Dirk Helbing, Bruno S. Frey, Gerd Gigerenzer, Ernst Hafen, Michael Hagner, Yvonne Hofstetter, Jeroen van den Hoven, Roberto V. Zicari, Andrej Zwitter -- Digital Fascism Rising?, by Dirk Helbing -- The Birth of a Digital God, by Dirk Helbing -- To the Elites of the World: Time to Act, by Dirk Helbing -- Why We Need Democracy 2.0 and Capitalism 2.0 to Survive, by Dirk Helbing -- How to Make Democracy Work in the Digital Age, by Dirk Helbing and Stefan Klauser -- The Blockchain Age: Awareness, Empowerment and Coordination, by Jeroen van den Hoven, Johan Pouwelse, Dirk Helbing and Stefan Klauser -- From War Rooms to Peace Rooms: A Proposal for the Pro-Social Use of Big Data Intelligence, by Dirk Helbing and Peter Seele -- New Security Approaches for the 21st Century: How to Support Crowd Security and Responsibility, by Dirk Helbing -- Homo Socialis: The Road Ahead, by Dirk Helbing -- Social Mirror: More Success through Awareness and Coordination, by Dirk Helbing -- Digitization 2.0: A New Game Begins, by Dirk Helbing.
Keywords: Sociology; Political science; System theory; Dynamics; Nonlinear theories; Sociology -- Methodology; Physics -- Study and teaching; Sociology; Politics and International Studies; Complex Systems; Applied Dynamical Systems; Sociological Methods; Education in Physics